P67 "Being with people like me": Missed opportunities for maximising the benefits of group self-management programs. (13th September 2016) - Hughes, SJ; Smith, L; Willis, K; Lewis, S; Rogers, A; Franklin, M
Abstract : Background: Group programs for people with chronic conditions led by health care practitioners (HCPs) have been promoted as a way of achieving positive public health outcomes. These groups promote behaviour change through education, increasing individual self-efficacy and goal setting. Existing research has focussed on measuring the impact of these programs on clinical and psychosocial outcomes, however there is little exploration on how social determinants shape these outcomes or how 'incidental' benefits are accrued by the participants. The aim of this study was to explore, from the perspective of both health care providers delivering the programs, and participants in the programs, how people experience participation in group programs. Methods: A qualitative study of participation in group programs in Australia for diabetes type 2, COPD, and obesity was undertaken. Participant observations of group sessions were conducted. Following this, in-depth semi-structured interviews were conducted with HCPs facilitating the group and with participants in the group. Interviews were audio-recorded, transcribed and analysed using inductive thematic analysis. Results: There were differences between the experiences of the HCP facilitators and the group participants. Facilitators focussed on creating an environment which provided education and information, and encouraged participants to formulate tangible self-management goals. The emphasis was on achieving improvement through measurable outcomes. Encouraging group members to share their experiences, despite being advocated by the facilitators, was absent in practice. In contrast, and integral to the participants' experience, was the notion of 'being with people like me'. Participants spoke of valuing the group experience through 'having a place with freedom from stigma and shame', 'realising I am not alone', 'enabling us to be ourselves', 'a place to not feel like a burden', and 'comparison with others'. Social factors, such as gender and age also shaped participants' experiences of the group. Conclusion: There is a gap between the facilitators of group programs for people with a chronic condition and the participants. By focussing on an instrumental change model, facilitators miss opportunities for the achievement of social benefits valued by participants. Group programs are a cost effective way of delivering public health benefits for people with chronic conditions. Implementing a more socially oriented model has the potential to deliver outcomes that meet the needs of both facilitator and participant.